Structure-based design of a new series of N-(piperidin-3-yl)pyrimidine-5-carboxamides as renin inhibitors. Issue 22 (15th November 2016) - Imaeda, Yasuhiro; Tawada, Michiko; Suzuki, Shinkichi; Tomimoto, Masaki; Kondo, Mitsuyo; Tarui, Naoki; Sanada, Tsukasa; Kanagawa, Ray; Snell, Gyorgy; Behnke, Craig A.; Kubo, Keiji; Kuroita, Takanobu
Graphical abstract: Abstract: The action of the aspartyl protease renin is the rate-limiting initial step of the renin-angiotensin-aldosterone system. Therefore, renin is a particularly promising target for blood pressure as well as onset and progression of cardiovascular and renal diseases. New pyrimidine derivatives5 –14 were designed in an attempt to enhance the renin inhibitory activity of compound3 identified by our previous fragment-based drug design approach. Introduction of a basic amine essential for interaction with the two aspartic acids in the catalytic site and optimization of the S1/S3 binding elements including an induced-fit structural change of Leu114 ('Leu-in' to 'Leu-out') by a rational structure-based drug design approach led to the discovery of N -(piperidin-3-yl)pyrimidine-5-carboxamide14, a 65, 000-fold more potent renin inhibitor than compound3 . Surprisingly, this remarkable enhancement in the inhibitory activity of compound14 has been achieved by the overall addition of only seven heavy atoms to compound3 . Compound14 demonstrated excellent selectivity over other aspartyl proteases and moderate oral bioavailability in rats.